2012
DOI: 10.2903/j.efsa.2012.2457
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 21, Revision 3 (FGE.21Rev3): Thiazoles, thiophenes, thiazoline and thienyl derivatives from chemical groups 29 and 30

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids of the European Food Safety Authority was requested to evaluate 59 flavouring substances in the Flavouring Group Evaluation 21, including an additional three substances in this Revision 3, using the Procedure in Commission Regulation (EC) No 1565/2000. Since the publication of the last revision of this FGE, the EFSA has been requested to evaluate three additional substances 15.079 and 15.135], which have been included in the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Application of the Procedure to 59 Thiazoles, Thiophene, Thiazoline and Thienyl Derivatives and Miscellaneous Substances from Chemical Group 30 by EFSA (FGE.21Rev3) (EFSA CEF Panel, 2012 (JECFA, 1995;JECFA, 1996;JECFA, 1997;JECFA, 1999), hereafter named the "JECFA Procedure". The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (the Panel) compares the JECFA evaluation of structurally related substances with the result of a corresponding EFSA evaluation, focussing on specifications, intake estimations and toxicity data, especially genotoxicity data.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the Procedure to 59 Thiazoles, Thiophene, Thiazoline and Thienyl Derivatives and Miscellaneous Substances from Chemical Group 30 by EFSA (FGE.21Rev3) (EFSA CEF Panel, 2012 (JECFA, 1995;JECFA, 1996;JECFA, 1997;JECFA, 1999), hereafter named the "JECFA Procedure". The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (the Panel) compares the JECFA evaluation of structurally related substances with the result of a corresponding EFSA evaluation, focussing on specifications, intake estimations and toxicity data, especially genotoxicity data.…”
Section: Discussionmentioning
confidence: 99%
“…Derivatives of thiazine and dithiazine, like 5,6-dihydro-2,4,6-trans(2-methylpropyl)4H-1, 3, 5-dithiazine [15.113], are expected to be metabolised primarily via side-chain oxidation and by ring S-and N-oxidation (EFSA CEF Panel, 2012a).…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%
“…For the remaining substance 3-(methylthio)-methylthiophene .126], supported by FGE.21 subgroup A-Ic, since no genotoxicity data were available on the substance, the Panel referred to the EFSA conclusion on the substances considered in group A-Ic in FGE.21Rev3 (EFSA, 2012b). For this subgroup A-Ic, EFSA had concluded that genotoxicity data were limited, but the data did not preclude evaluating the substances through the Procedure.…”
Section: Efsa Considerationsmentioning
confidence: 99%
“…The substances were allocated into structural subgroups (for description and explanation, see FGE.21Rev3 (EFSA, 2012b) and were evaluated at step B4 in the Procedure, i.e. the substances are not expected to be metabolised to innocuous products and the estimated intakes are below the thresholds for their structural classes II and III.…”
Section: Application Of the Procedures To Sulphur Containing Heterocycmentioning
confidence: 99%